MODEL INNOMATTS UNTUK MENINGKATKAN KETRAMPILAN GURU MATEMATIKA SMP DALAM MENERAPKAN PENDEKATAN SAINTIFIK DAN PENILAIAN AUTENTIK - Junaedi, I.; Asikin, M. (Universitas Negeri Semarang, 2015)
This article to study how mathematics teacher to applies scientific approach and authentic assessment corresponds to curriculum 2013? Method that are utilized to know mathematics teacher in applies scientific approach and authentic assessment are done with training, assistance, observation, and interview. Based on observing and analisis are known (1 ) Lesson Plan with INNOMATTS’S models for scientific approach and authentic essessment that arranged by category “good ”, (2) teacher ability increaces, and (3 ) student response for active, criticak, and collaboration increases.